Correction: The Toponymy of the Argentine Islands area, the Kyiv Peninsula (West Antarctica) - Yevchun, H.; Fedchuk, A.; Drohushevska, I.; Pnyovska, O.; Chernyshenko, M.; Parnikoza, I. (Ukrainian Antarctic Journal, 2022)
Author Correction: Yevchun, H., Fedchuk, A., Drohushevska, I., Pnyovska, O., Chernyshenko, M., & Parnikoza, I. (2021). The Toponymy of the Argentine Islands area, the Kyiv Peninsula (West Antarctica). Ukrainian Antarctic Journal, 2, 127—157.